2020
DOI: 10.21608/alexja.2020.90853
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Different Application Methods and Concentrations of Ascorbic Acid on Sugar Beet under Salinity Stress Conditions

Abstract: Salinity is one of the major abiotic stresses which affected on plant growth and reduces plant productivity. Antioxidants compounds considered as one of the methods and strategies to ameliorate the deleterious effects of salinity stress on plants to reduce the effect of oxidative stress. Field experiment was carried out at Sinnuris District which located mainly adjacent to Lake Qarun (saline soil) at El Fayoum Governorate (latitude 29°20 and 29°30 N and longitude 30°43 and 30°56 E) during 2015/2016 and 2016/20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…A field experiment with sugar beet (Beta vulgaris var. saccharifera, L.) under salt stress showed that soaking the seeds plus foliar spraying with ascorbic acid increased the enzymatic activity of CAT and SOD, as well as root yield and sugar content (Abdel Fatah and Sadek, 2020). In another work, both vitamin C and B 3 alleviated the effects of salt stress, but vitamin B 3 was more effective, and in combination they were synergistic (Azooz et al, 2013).…”
Section: Vitaminsmentioning
confidence: 99%
“…A field experiment with sugar beet (Beta vulgaris var. saccharifera, L.) under salt stress showed that soaking the seeds plus foliar spraying with ascorbic acid increased the enzymatic activity of CAT and SOD, as well as root yield and sugar content (Abdel Fatah and Sadek, 2020). In another work, both vitamin C and B 3 alleviated the effects of salt stress, but vitamin B 3 was more effective, and in combination they were synergistic (Azooz et al, 2013).…”
Section: Vitaminsmentioning
confidence: 99%